Presence of Staphylococcus aureus after surgical hand washing in dentistry students - Melissa de la Vega Arana; Carlos Cava Vergiú (Kiru)
Objetive: The objective of the present study was to determine the presence of Staphylococcus aureus in the students of the course of Surgery Buco Máxilo Facial I of the Faculty of Dentistry-USMP after the surgical hand washing. Materials and Methods: Students were divided into 4 groups: Group A: Students who performed the technique of surgical hand-washing with a brush using chlorhexidine soap, Group B: Students who performed the technique of surgical hand washing by friction (without brush) using chlorhexidine soap, Group C: Students who performed the technique of surgical hand-washing with a brush using glycerin soap, Group D: Students who performed the technique of surgical hand washing by friction (without brush) using glycerin soap. In each group the presence of Staphylococcus aureus was determined and compared between the four. Results: In all of groups there was presence of Staphylococcus aureus, but in the technique of group B there was less quantity. Conclusions: Many people are carriers of Staphylococcus aureus in their hands. The most recommended surgical hand washing technique is the friction technique (without brush), using chlorhexidine soap.